ANALISIS PENGEMBANGAN KEPROFESIAN BERKELANJUTAN GURU SEKOLAH DASAR - Henryk P. Gonsales; Debora M.V. Krowin; Apriliani Kartini; Aprilis Y. Tefu; Bintang E.P. Sabah; Allan Killa; Jebri M. Lassa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Continuing Professional Development (CPD) is a strategic instrument for systematically and sustainably improving teacher professionalism. CPD emphasizes not only pedagogical competence but also professional, social, and personal competencies, enabling teachers to adapt to changes in 21st-century education. The integration of CPD with technology-based learning innovations has been shown to increase the effectiveness of the learning process, teacher creativity, and student motivation. However, the implementation of CPD in Indonesia still faces various obstacles, including high teacher workloads, low digital literacy, lack of institutional support, limited implementation time, and low teacher self-confidence. This study uses a qualitative approach through a literature review to analyze the concept, implementation, challenges, and solutions of CPD integrated with learning innovations. The results of the study indicate that the implementation of systematic strategies including structured CPD planning, optimizing teacher time, strengthening digital literacy, integrating CPD with learning innovations, increasing policy support, enhancing teacher self-confidence, and continuous monitoring and evaluation can overcome obstacles to CPD implementation. Thus, PKB can be implemented effectively, improving teacher professionalism, encouraging creativity, and producing more innovative learning according to student needs.